2020
DOI: 10.3390/cells9040929
|View full text |Cite
|
Sign up to set email alerts
|

The Endothelium as a Driver of Liver Fibrosis and Regeneration

Abstract: Liver fibrosis is a common feature of sustained liver injury and represents a major public health problem worldwide. Fibrosis is an active research field and discoveries in the last years have contributed to the development of new antifibrotic drugs, although none of them have been approved yet. Liver sinusoidal endothelial cells (LSEC) are highly specialized endothelial cells localized at the interface between the blood and other liver cell types. They lack a basement membrane and display open channels (fenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 281 publications
(360 reference statements)
1
87
0
2
Order By: Relevance
“…On the other hand, after sustained liver injury from this progress, liver sinusoidal endothelial cells (LSECs) lose their phenotype and protective properties, promoting angiogenesis and vasoconstriction. It further contributes to repeating inflammation and triggers fibrosis [ 7 ]. All these actions will contribute to HSCs activation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, after sustained liver injury from this progress, liver sinusoidal endothelial cells (LSECs) lose their phenotype and protective properties, promoting angiogenesis and vasoconstriction. It further contributes to repeating inflammation and triggers fibrosis [ 7 ]. All these actions will contribute to HSCs activation.…”
Section: Introductionmentioning
confidence: 99%
“…LSECs govern initiation of the regenerative process initiation, and aberrant LSEC activation in chronic liver injury induces fibrosis. Sustaining hepatic injury can lead to loss of the LSEC phenotype and protective properties, promote angiogenesis and vasoconstriction, and contribute to inflammation and fibrosis [27]. Shubham et al [28] found that cellular and functional loss of liver endothelial cells correlates with poor hepatocyte regeneration in ACLF.…”
Section: Discussionmentioning
confidence: 99%
“…LSECs govern initiation of the regenerative process initiation, and aberrant LSEC activation in chronic liver injury induces brosis. Sustaining hepatic injury can lead to loss of the LSEC phenotype and protective properties, promote angiogenesis and vasoconstriction and contribute to in ammation and brosis (27). Shubham et al (28) found that cellular and functional loss of liver endothelial cells correlates with poor hepatocyte regeneration in ACLF.…”
Section: Discussionmentioning
confidence: 99%